2021
DOI: 10.1111/pce.14131
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐responsiveness of leaf isoprene emission: Why do species differ?

Abstract: Leaf isoprene emission rate, I, decreases with increasing atmospheric CO 2 concentration with major implications for global change. There is a significant interspecific variability in [CO 2 ]-responsiveness of I, but the extent of this variation is unknown and its reasons are not understood. We hypothesized that the magnitude of emission reduction reflects the size and changeability of precursor pools responsible for isoprene emission (dimethylallyl diphosphate, DMADP and 2-methyl-erythritol 2,4-cyclodiphospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 86 publications
(188 reference statements)
3
4
0
Order By: Relevance
“…While CO 2 responsiveness of isoprene emission varies among the species, we observed a 42% decrease in isoprene emission from poplar leaves at elevated CO 2 ( Fig. 1 B ), which corresponded to previous findings ( 31 33 ). Our data also indicate that CO 2 -mediated suppression of isoprene emission is independent of stomatal conductance ( SI Appendix , Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While CO 2 responsiveness of isoprene emission varies among the species, we observed a 42% decrease in isoprene emission from poplar leaves at elevated CO 2 ( Fig. 1 B ), which corresponded to previous findings ( 31 33 ). Our data also indicate that CO 2 -mediated suppression of isoprene emission is independent of stomatal conductance ( SI Appendix , Fig.…”
Section: Discussionsupporting
confidence: 91%
“…ATP and NADPH levels are reduced during feedback inhibition of photosynthesis by high CO 2 due to triose phosphate utilization (TPU) limitation of photosynthesis ( 27 , 28 ), which could result in lower DMADP levels, reducing the rate of isoprene emission. This is supported by multiple studies showing that isoprene emission is correlated with the DMADP levels in plant tissues ( 29 31 ). However, Lantz et al ( 22 ) demonstrated that suppression of isoprene emission at high CO 2 is not correlated with TPU limitation.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…Surprisingly, in R. frangula , the impact of P. coronata on mono- and sesquiterpenes was minor, but the emissions of isoprene were enhanced ( Figure 1B ). This might indicate both the overall upregulation of the chloroplastic methyl-D-erythritol phosphate (MEP) pathway for isoprenoid synthesis or isoprene synthase activity 7 , 17 , 41 , 42 . Apparently, the stress threshold for elicitation of terpene synthesis was not exceeded in the alternate host, or R. frangula has an overall low capacity for induction of terpene emissions.…”
Section: Differences In Fungal Activation Of Volatile Synthesis Pathw...mentioning
confidence: 99%
“…In addition, host differences in the expression of constitutive defenses and capacity to induce defense responses can result in divergent elicitation of volatile emissions in different host species 2 . Regarding volatiles, variations in the degree of constitutive isoprene emissions can give rise to differences in the induction of emissions of stress-elicited isoprenoids in different hosts 5 , 7 , 14 , 17 .…”
Section: Introductionmentioning
confidence: 99%